2021
DOI: 10.3233/jad-201113
|View full text |Cite
|
Sign up to set email alerts
|

Association Between APOE Alleles and Change of Neuropsychological Tests in the Long Life Family Study

Abstract: Background: The Long Life Family Study (LLFS) is a family based, prospective study of healthy aging and familial longevity. The study includes two assessments of cognitive function that were administered approximately 8 years apart. Objective: To test whether APOE genotype is associated with change of cognitive function in older adults. Methods: We used Bayesian hierarchical models to test the association between APOE alleles and change of cognitive function. Six longitudinally collected neuropsychological tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Our findings are consistent with previous studies that showed a decline of cognitive function with older age in multiple domains (Harada et al, 2013), and the negative effect of APOE e4 on cognitive decline in centenarians (Arosio et al, 2017;Du et al, 2020). There is some evidence that, among centenarians, the e2 allele confers protection from cognitive decline (Kim et al, 2017;Sebastiani et al, 2020), in addition to increasing the chance for longevity (Sebastiani et al, 2019a) and conferring protection from aging-related diseases (Wolters et al, 2019;Kuo et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with previous studies that showed a decline of cognitive function with older age in multiple domains (Harada et al, 2013), and the negative effect of APOE e4 on cognitive decline in centenarians (Arosio et al, 2017;Du et al, 2020). There is some evidence that, among centenarians, the e2 allele confers protection from cognitive decline (Kim et al, 2017;Sebastiani et al, 2020), in addition to increasing the chance for longevity (Sebastiani et al, 2019a) and conferring protection from aging-related diseases (Wolters et al, 2019;Kuo et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Although the association between APOE ε4 and long-term memory has been established, [14][15][16][17][18] the extent to which APOE ε4 may impact other domains of cognitive functioning is commonly studied. Some studies indicate that APOE ε4 carriers exhibit deficits in psychomotor speed, 19,20 attention, 21,22 working memory, [21][22][23] and learning 16,[24][25][26] compared to non-carriers. However, some studies did not observe a significant effect of APOE ε4 on psychomotor speed and attention.…”
Section: Introductionmentioning
confidence: 99%
“…It yields results with parsimonious parameters with practical meaning and can achieve computational efficiency. In addition to the application example in this paper, we have also implemented this proposed algorithm in analyzing the association between familial longevity and cognitive decline, and the association between APOE allele and cognitive decline in the Long Life Family Study (LLFS) Andersen et al 2020; Du et al (2020). Method CI DIC CI DIC CI DIC CI DIC CI DIC CI DIC CI DIC CI DIC Correct Model 100 100 100 3 100 100 99 9 100 100 100 25 74 87 100 37 1 Mismatch 0 0 0 30 0 0 0 32 0 0 0 36 26 13 0 43 2 Mismatch 0 0 0 37 0 0 1 34 0 0 0 27 0 0 0 18…”
Section: Resultsmentioning
confidence: 99%